Cross section of the cut layer in oblique single-edge boring by a radial cutter; Russian Engineering Research; Vol. 37, iss. 4 - Filippov A. V. Andrey Vladimirovich; Shamarin N. N. Nikolay Nikolaevich; Podgornykh O. A. Oleg Anatolievich; Chazov P. A. Pavel Andreevich (2017, 2017)
Title screen